Determinan Kualitas Laporan Keuangan Pemerintah Daerah - Veny Mufidatus Saffanah; Dwi Suhartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to empirically prove the influence of human resource competence, use of information technology and implementation of the government's internal control system on the quality of local government financial reports. This research is quantitative research with primary data through distributing questionnaires. The population used in this research was all BPPKAD Gresik Regency employees totaling 108 employees. By using the purposive sampling method in selecting the sample, it resulted in 41 employees who met certain criteria. The analysis technique used is Partial Least Square (PLS) using SmartPLS 4.0 software. The research results show that human resource competence, use of information technology and implementation of the government's internal control system are able to improve the quality of local government financial reports.